2020
DOI: 10.1016/j.actbio.2019.12.034
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium phosphate surface structure in osteogenesis and the mechanisms involved

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(118 citation statements)
references
References 131 publications
3
101
0
1
Order By: Relevance
“…Previous studies have confirmed that HA-modified Ti surfaces can promote cell differentiation and maturation in vitro [ [50] , [51] , [52] , 62 ], and also, HA-deposited implants were able to induce bone ingrowth at the bone-implant interface without isolation by fibrous tissue layer in vivo [ 20 , [63] , [64] , [65] , [66] ]. Although the detailed mechanism is still under exploration, the superior bioactivity and osteoconductivity of HA are related to its physicochemical properties, such as composition, morphology and geometry [ 16 , 20 , 67 ]. Moreover, the release of calcium and phosphate ions from HA into the cell-material microenvironment probably enhanced the ALP activity and extracellular matrix mineralization [ 16 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have confirmed that HA-modified Ti surfaces can promote cell differentiation and maturation in vitro [ [50] , [51] , [52] , 62 ], and also, HA-deposited implants were able to induce bone ingrowth at the bone-implant interface without isolation by fibrous tissue layer in vivo [ 20 , [63] , [64] , [65] , [66] ]. Although the detailed mechanism is still under exploration, the superior bioactivity and osteoconductivity of HA are related to its physicochemical properties, such as composition, morphology and geometry [ 16 , 20 , 67 ]. Moreover, the release of calcium and phosphate ions from HA into the cell-material microenvironment probably enhanced the ALP activity and extracellular matrix mineralization [ 16 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the detailed mechanism is still under exploration, the superior bioactivity and osteoconductivity of HA are related to its physicochemical properties, such as composition, morphology and geometry [ 16 , 20 , 67 ]. Moreover, the release of calcium and phosphate ions from HA into the cell-material microenvironment probably enhanced the ALP activity and extracellular matrix mineralization [ 16 , 67 ]. Ca 2+ ion plays an important role in modulating cellular functions through specific sites and receptors, including calcium-related proteins (e.g., pancreatic stone protein), extracellular matrix proteins (e.g., fibulin) and gene-associated signaling (e.g., SOX9) [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…A rough surface can promote cell adhesion and differentiation; however, increasing roughness can lead to cell death. In this review the authors also reported that surface structure impacts osteogenesis by interacting with protein adsorption, cilia modulation and the immune response[136].It appears clearly that the surface properties of materials strongly influence processes involved in osteogenesis and therefore the osteointegration of orthopedic biomaterials. In a more general context, the biological response depends on a complex interaction between patient-related aspects (age, gender, metabolism, …), material properties (architecture, biodegradation, composition, porosity, …) and induced biological responses (cell adhesion and proliferation, protein adhesion, …)[137].…”
mentioning
confidence: 87%
“…Calcium phosphates (especially hydroxyapatite) have a high affinity for BMP (bone morphogenetic proteins), can osseointegrate, osseoconduct, and favor new bone tissue formation; therefore, they have been the main component of numerous studies, along with natural polymers (e.g., collagen, chitosan, gelatin and silk) [13,14]. The major disadvantages of these composite scaffolds are their slow biodegradability, reduced mechanical properties and potential toxicity, which restrict their clinical applications [15][16][17].…”
Section: Introductionmentioning
confidence: 99%